Detecting intimal tear and subintimal blood flow of thrombosed acute aortic dissection with ulcer-like projections using non-obstructive angioscopy. Issue 5 (November 2018) - Takahashi, Satoru; Komatsu, Sei; Ohara, Tomoki; Takewa, Mitsuhiko; Toyama, Yasuyuki; Yutani, Chikao; Kodama, Kazuhisa
Abstract: A 73-year-old man reporting severe chest and back pain for 20 min was admitted to our hospital. The pain occurred 3 days before admission. Computed tomography angiography showed a hazy-surfaced low-density area in the aortic arch with aneurysmal formation of unknown etiology. It was inconclusive whether the aortic change was acute or chronic because no previous information was available. To investigate the etiology, non-obstructive angioscopy (NOA) was performed. A fissure with blood flow was detected at the surface of the low-density area and active subintimal blood flow was demonstrated on NOA. An entry tear and active blood flow below the intima at the seemingly thrombosed area suggested that the patient had a thrombosing type B aortic dissection. <Learning objective: A 73-year-old man reporting severe chest and back pain for 20 min was admitted to our hospital, occurring 3 days before admission. Computed tomography angiography (CTA) was inconclusive, showing a hazy-surfaced low-density area in the aortic arch with aneurysm formation. Non-obstructive angioscopy detected a disrupted intima, including entry of the dissection and active subintimal blood flow. The patient was diagnosed with thrombosed type B aortic dissection. Apparent flow inside the low-density area was missed on CTA.>